Determinan sosial ekonomi ketimpangan gender provinsi-provinsi di Pulau Sumatera - Marsyandy Putri, Amanda; Junaidi, Junaidi; Kusuma Edy, Jaya (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2025)
This study aims to determine and analyze the development of gender inequality. In addition, to determine the conditions and effects of life expectancy, average length of schooling, and adjusted per capita expenditure on gender inequality in provinces on the island of Sumatra. This study applies quantitative analysis, namely panel data regression analysis with a period of 2017-2022 and 10 provinces on the island of Sumatra. The results of this study explain that the dynamics of gender inequality fluctuate every year. The highest Gender Inequality Index value is in the Bangka Belitung Islands Province at 0.587 while the lowest is in the Riau Islands Province at 0.330. The Riau Islands Province has the highest average development while the lowest average development is Lampung Province. Partially, the variables of life expectancy and average length of schooling do not affect gender inequality. While the adjusted per capita expenditure variable affects gender inequality.